Aplikasi Pembelajaran Percakapan Bahasa Arab dan Inggris Berbasis Android - Hairani Hairani; Muhammad Zulkarnaen Haris; Muhammad Arfa; Muhammad Innuddin (Universitas Bumigora, 2022)
Nurul Haramain Islamic Boarding School NW Narmada is a private educational institution that applies English and Arabic as daily languages ​​for students in the boarding school environment. However, students who have just entered the Islamic boarding school are given up to six months to learn English and Arabic. Until now, Nurul Haramain Islamic Boarding School NW Narmada in teaching Arabic and English to students still uses the conventional learning process without using the help of learning media. Most of the students did not listen to the teacher delivering the subject matter, difficulties in understanding the material, and the lack of interest of the students in Arabic and English conversations. Therefore, this study aims to develop an application for learning conversational English and Arabic based on Android for class 1 students of Mts Nurul Haramain. The application development stages use the Luther Sutopo model which consists of the Concept, Design, Material Collecting, Assembly, Testing, and Distrubution stages. The application that has been developed was tested on 30 respondents related to application functionality, where the results of application functionality were 78% in the Good category, so that it can help class 1 students of Mts Islamic boarding school Nurul Haramain learn English and Arabic conversation with the correct pronunciation.